PENGARUH PERBANDINGAN KONSENTRASI ASAM ASETAT DAN ASAM SITRAT TERHADAP KARAKTERISTIK PIKEL CABAI PIMIENTO (Capsicum chinense) - Devi Pradnyanita, AA.; Mayun Permana, I Dewa Gede; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 6 No 1 (2017): Jurnal ITEPA)
This study was aimed to combination effect of acetic acid and citric acid concentrations on the chili pimiento pickle characteristics and to obtain optimum concentrations which produce the best characteristics. This study was designed using randomized block factorial with two factors, the first factor was concentration of acetic acid (1%, 1.5%, 2%), and the second factor was concentration of citric acid (0.1%, 0.15 %, 0.2%) and all data were analyzed statistically using ANOVA and continued by DMRT ( Duncan Multiple Range Test ). The result showed that the acetic acid factor influenced vitamin C and sensory characteristics (taste and aroma). Citric acid influenced vitamin C antioxidant activity and sensory characteristics (taste and aroma) in pickle pimiento. The best characteristics was found on treatment 1.5% actic acid and 0.15%citric acid with vitamin C 25.14%, antioxidant activity 58.68%, pH 3.35, with color L*a*b* , L * indicates Light / light, a * are the coordinates of red / green, and b * are the coordinates of the yellow / blue (15.99, 6.67, 55.16) was red and liked, aroma was slightly vinegar and liked, taste was typical pickle and liked, texture was slightly hard and slightly liked, and overall acceptance was liked.
Keywords: antioxidant, citric acid, acetic acid, pimiento chili and pickle